Sarmata w ogrodach Europy i Bliskiego Wschodu - Jarczykowa, Mariola (Śląskie Studia Polonistyczne, 2018)
The article presents the accounts of Polish diarists’ overseas travels (16th–17th century), which include descriptions of parks and gardens. The authors: Mikołaj Krzysztof Radziwiłł “Sierotka” and Karol Stanisław Radziwiłł, Krzysztof Zawisza, Jan Ocieski, Teodor Billewicz, Maciej Rywocki, and others marvelled at the impressive gardens and bestiaries in France, Italy, Spain and the Holy Land. In the travellers’ accounts – diverse in terms of their attention to detail – there appeared descriptions of gardens, their location and arrangement, together with some opinions and evaluations made by the authors. What drew their particular attention and admiration were magnificent fountains, exotic plants and animals.